The relationship between clinical perfectionism and nonsuicidal self-injury: The roles of experiential avoidance, self-esteem, and locus of control - Duncan-Plummer, Thomas; Hasking, Penelope; Tonta, Kate; Boyes, Mark (2023)
Objectives: Perfectionism is linked to nonsuicidal self-injury (NSSI). Individuals with elevated perfectionism tend to avoid undesirable emotions and experience lower self-esteem, which are associated with NSSI. However, it is unclear if these mechanisms explain the link between clinical perfectionism and NSSI, and if locus of control is involved. We aimed to explore whether experiential avoidance and self-esteem would mediate the relationship between clinical perfectionism and NSSI, and if locus of control would moderate links between clinical perfectionism and both experiential avoidance and self-esteem. Method: As part of a larger study, 514 Australian university students (Mage = 21.15 years, SD = 2.40; 73.5% female) completed an online survey of NSSI, clinical perfectionism, experiential avoidance, self-esteem, and locus of control. Results: Clinical perfectionism was associated with NSSI history, but not with recent NSSI or past year NSSI frequency. Lower self-esteem, but not experiential avoidance, mediated links between clinical perfectionism and NSSI history, recent NSSI, and NSSI frequency. More external locus of control was associated with NSSI, experiential avoidance, and lower self-esteem, but locus of control did not moderate pathways between clinical perfectionism and experiential avoidance or self-esteem. Conclusion: University students reporting elevated clinical perfectionism may have a tendency to experience lower self-esteem which is associated with NSSI history, recency, and severity.